Growth, leaf gaseous exchange and nutritive value of selected summer forage legumes and their contributions to succeeding winter grass (Secale cereale) in District Agro-ecological zone of Limpopo Province - Lekgothoane, Philemon Lesetja (My University, 2022)
In South Africa, livestock production is a rapidly growing business in the agricultural sector contributing up to 46.9% of the gross domestic value. The shortage of adequate, good quality forage during the winter months is one of the biggest problems confronting livestock farmers in the Limpopo Province. This study was initiated in 2019 to evaluate the production potential and nutritive value of different summer annual forage legumes, namely sunnhemp (Crotalaria juncea), forage cowpea (Vigna unguiculata), lablab bean (Lablab purpureus), and pigeon pea (Cajanus cajans), and their impact on succeeding winter stooling ryegrass (Secale cereale), at the University of Limpopo experimental farm Syferkuil and a Cooperative farmers’ field at Ofcolaco. The study was evaluated in a randomized complete block design with four replications. Dry matter yield, crude protein, crude protein yield, leaf chlorophyll content, Normalized Difference Vegetative Index (NDVI), and leaf gaseous exchange parameters of forage crops were statistically analysed with Statistical Analysis System (SAS), Enterprise Version 9.4, using the least significant difference (LSD) method for mean comparison. Pigeon pea biomass accumulation was 57% lower than the average of the three other legumes at Syferkuil. Sunnhemp produced superior biomass (P<0.05) compared to the other three species, reaching a peak yield of 3142.4 kg.ha-1 and 8970.8 kg ha-1 at Syferkuil and Ofcolaco, respectively. Cowpea and lablab produced similar biomass at Syferkuil. The crude protein content of the forage species ranged from 22.91% to 26.82% at Syferkuil and 17.03% to 23.84% at Ofcolaco. Leaf chlorophyll content differed (P<0.001) among the forage legume species at both locations with cowpea producing the highest chlorophyll content at Syferkuil, whereas at Ofcolaco, pigeon pea constantly produced the highest chlorophyll compared to other species. Pigeon pea was the only species rated moderately healthy with Normalised Difference Vegetative Index (NDVI) readings at Syferkuil, unlike at Ofcolaco where all forage legumes were rated as very healthy. At Syferkuil, no root nodules were observed among all the forage legumes at all sampling dates but at Ofcolaco, nodules were produced at 44 DAE with cowpea producing the highest, 92.32% higher than the average of sunnhemp, lablab, and pigeon-pea. At this location pigeon pea did not nodulate. The transpiration rate at Syferkuil was significant (P<0.01) among the species starting with a low transpiration rate from 24 days after planting and reaching their peak at 66DAE. Overall, pigeon pea had the highest (P<0.05) mean transpiration rate compared to the other species. At Ofcolaco the forage legume treatment did not have any significant (P>0.05) influence on transpiration rate, stomatal conductance and sub-stomatal conductance. The transpiration rate of the species ranged from 0.1 mol m-2 s -1 to 5.15 mol m-2 s -1 across all sampling dates whereas stomatal conductance ranged from 0.06 to 5.59 mol m-2 s -1 at Syferkuil and 0.1 to 5.15 mol m-2 s -1 at Ofcolaco, across all sampling dates and species. At Syferkuil, the mean stomatal conductance values ranged from 129.75 mol m-2 s -1 to 374 mol m-2 s -1 across the sampling dates and species, whereas, at Ofcolaco, the means ranged from 185 mol m-2s -1 to 390.25 mol m-2s -1 . The succeeding stooling rye produced a similar biomass yield under every preceding forage legume. This can be concluded that all the four forage legumes did not have any effect on the biomass production of stooling rye. However, there appeared to be a tendency of higher biomass production in the grass species grown after pigeon pea and lablab compared to those following sunnhemp and cowpea. Further experiments are required to establish the full benefits of the forage legumes on succeeding forage grass crop. Based on the results from this study, it was concluded that sunnhemp can be considered as the first choice forage legume at both Syferkuil and Ofcolaco due to its consistently high biomass production, comparable nutrient profile, high crude protein content and high protein yield compared with the other legumes. Though sunnhemp was superior, the other forage summer legumes species studied also managed to produce enough biomass for grazing and had similar nutritive value which was above minimum recommendations. They can therefore be cultivated in the province to meet the constraint of the feed gap in the province. Additional studies at different locations, however, will help to understand the productivity of the species and also to establish the full benefits of the forage legumes on succeeding forage grass crops
Thesis (M.Sc. (Pasture Science)) -- University of Limpopo, 2022
Keywords: Dry matter yield; Chemical composition; Forage legume; Forage plants; Legumes; Field crops